Natural disasters in the Ottoman Empire : halcyon days in Crete III, a symposium held in Rethymnon 10-12 January 1997 - Ζαχαριάδου, Ελισάβετ Α. (Halcyon days in Crete, 1999)
A natural disaster, such as an earthquake or a flood, sometimes followed by a second disaster, such as fire or an epidemic, constitutes an unforeseen event which has an impact on a society's economy or demography and often on the relations of the individual with the state or the religious authorities. Nevertheless, the role of natural disasters in historical developments is ambiguous. The nineteen studies included in this volume deal with methodology for the study of natural disasters and with the problems mentioned above.